Value of the Overall Pneumococcal Polysaccharide Response in the Diagnosis of Primary Humoral Immunodeficiencies - Lopez, Benjamin; Bahuaud, Mathilde; Fieschi, Claire; Mehlal, Souad; Jeljeli, Mohamed; Rogeau, Stéphanie; Brabant, Séverine; Deleplancque, Anne-Sophie; Dubucquoi, Sylvain; Poizot, Sandrine; Terriou, Louis; Launay, David; et al. (Frontiers in Immunology, 2017)
Background: An overall response assay (OVA, based on a 23-valent pneumococcal polysaccharide vaccine (PPV23)) is widely used to screen for antipneumococcal antibodies. Given the heterogeneity of response from one polysaccharide to another, a World Health Organization-standardized serotype-specific enzyme-linked immunosorbent assay (SSA) is considered to be the only reliable method for testing anti-polysaccharide antibody responses in individuals with suspected primary immunodeficiencies (PIDs). Objective: To evaluate the OVA relative to the reference SSA. Methods: Serum samples of adult patients referred for a suspected PID were collected before and then 4 to 8 weeks after immunization with PPV23. The antipneumococcal response was systematically assessed with an SSA (7 to 16 serotypes) and interpreted according to the American Academy of Asthma, Allergy and Immunology’s current guidelines. We used receiver operating characteristic curves and agreement indices to assess the OVA’s diagnostic value in a first cohort. In order to validate these findings, a second (validation) cohort was then prospectively included. Results: Sixty-two adult patients were included, and 42 (67.7%) were defined as poor responders according to the SSA. Only the post-immunization titer in the OVA was able to correctly identify poor responders; a titer below 110 mg/L gave a positive predictive value of 100% (identifying 24 (57.1%) of the 42 poor responders), and similar levels of diagnostic performance were observed in the validation cohort. The pre-vaccination antibody titer, the post/pre-vaccination antibody titer ratio and a post-vaccination titer above 110 mg/L in the OVA were not predictive of the response in the SSA. Conclusion: A post-vaccination antibody titer below 110 mg/L in the OVA was constantly associated with a poor PPV23 response using the SSA. In all other cases, SSA is the only reliable method for assessing diagnostic vaccination with PPV23.